Acervos arquivísticos em instituições esportivas, militares e religiosas de Santa Maria, RS - Sauter, Silviane Silveira (2019)
This study aims to able the diffusion of archives from sports, military and religious institutions of Santa Maria city, RS, through of the elaboration of a reference guide of files, informing researches and the socity in general about the content of these collections, their locations and the access conditions, such as the use of necessary documents to do so. The choice for the theme occurred to us due the need for a contribution to disseminate and promote the archives of public (military) and private (sports and religious institutions) institutions of Santa Maria, RS, since the memory preserved in these files enables the rescue of the institution's history and the local identity. The researched institutions are the following: Corintians Athletic Club, Historical Centre Coronel Pillar, Cathedral of Mediator, The Mginificat Institution – seat of the Legion of Holy Mary - Priest Francisco Mascarenhas Memorial, province Nossa Senhora Conquistadora, and the first Baptist Church in Santa Maria. Methodologically we choosed for a qualitative approach, through an exploratory, descriptive and bibliographical research. Also, at the same time that the preparation of the work and the identification of the holder institutions of historical collections of the religious, military and sports institutions of Santa Maria were taking place, a bibliographical research was carried out, considering references about: cultural and documental heritage, archive, memory and history, public and private archives of public and social interest, guides, and archival functions: description and diffusion. The results obtained were fundamental for the elaboration of the reference guide of Sports, Military and Religious archives of Santa Maria, RS, the main product of this Masters dissertation. As conclusion it became clear that the files studied are important sources for historical researches, and constitute an important piece of the cultural patrimony of Santa Maria.